A Resilient China Amid COVID-19 Pandemic Crisis: Innovative Lessons for Other Countries - Kayani, Farrukh Nawaz (International Journal of Economics and Financial Issues, 2022)
The outbreak of the Covid-19 pandemic deteriorated the paradigm of the global economy as the whole world had come to a standstill because of massive destructions being caused by this virus. Although the virus originated from China, but it soon spread across the world with its ability to infect the millions of people. The economic destruction, healthcare devastation, and political unrest caused by the pandemic were met with a critically tailored set of policies being designed by Chinese government. The pandemic resulted in a countrywide lockdown of China which led to the economic and political downfall of the country. Millions of people were infected within a short span of time leading to imposition of healthcare emergency by the government. Interestingly, China did not undergo a period of recession during this pandemic, but instead it underwent a prolonged period of economic stagnation as it did not suffer much like other economies of the world. Months after the pandemic had wreaked havoc, China started to gain stability as its efforts towards diffusing the situation proved successful in containing the virus. China being the first country to be struck with this pandemic naturally provides a foolproof plan for other countries to imitate in their struggle towards disease containment. This article has attempted to highlight the impact of the coronavirus pandemic upon China and how the government managed to control the transmission of this deadly virus to a great extent. Furthermore, what innovative and imitating lessons can be learnt by other countries from a resilient China.